A high‐pressure polymorph of chlorpropamide formed on hydrostatic compression of the α‐form in saturated ethanol solution. (24th January 2013) - Seryotkin, Yury V.; Drebushchak, Tatiana N.; Boldyreva, Elena V.
<x xml:space="preserve">Abstract</x> The crystal structure of the high‐pressure polymorph (α′) of an antidiabetic drug, chlorpropamide [4‐chloro‐N‐(propylaminocarbonyl)benzenesulfonamide, C10H13ClN2O3S], which is formed at ∼ 2.8 GPa from the α‐polymorph (P212121) on hydrostatic compression in saturated ethanol solution, has been determined. As a result of the phase transition, the a, c and α parameters change jumpwise, whereas the changes in b parameter are continuous through the phase transition point. The high‐pressure form is monoclinic (P2111) and has Z′ equal to 2, the two independent molecules differing in their conformations. The hydrogen bonds expand slightly in the high‐pressure polymorph after the transition, and this expansion is interrelated with the changes in molecular conformations enabling a denser packing. The transition is reversible, but the crystal quality deteriorates as a result of multiple compression–decompression cycles, and a pseudomerohedral twinning accompanies the transformation.